Multimodal imaging in infectious and noninfectious intermediate, posterior and panuveitis. Issue 3 (May 2021) - Thomas, Akshay S.; Lin, Phoebe
Abstract : Purpose of review: Given the heterogeneity of uveitis, markers of inflammation vary from patient to patient. Multimodal imaging has proven itself to be critical for accurate evaluation for disease activity and treatment response in uveitis. Recent findings: Ultra-widefield (UWF) fluorescein angiography and autofluorescence (AF) as well as optical coherence tomography angiography (OCTA) have provided insights into disease pathogenesis and monitoring not previously appreciated. In addition to structural retinal imaging, OCT can be used to assess the choroid, the posterior cortical vitreous and the retinal vasculature in eyes with uveitis. Summary: Multimodal ocular imaging in eyes with uveitis is critical for disease diagnosis and assessing response to treatment. UWF fluorescein angiography can detect retinal vasculitis even in the absence of overt vascular sheathing. UWF AF can help detect more chorioretinal lesions than clinically visible. OCT can be used to assess the posterior cortical vitreous, retina, large retinal vessels and choroid in uveitis. The use of multimodal imaging will likely be needed to determine clinical trial endpoints in studies evaluating therapeutics for uveitis.